SAT0043 SERUM BIOMOLECULES AS POTENTIAL BIOMARKERS OF CLINICAL EFFICACY AND PREDICTORS OF RESPONSE TO BIOLOGIC DISEASE MODIFYING ANTI-RHEUMATIC DRUGS IN RHEUMATOID ARTHRITIS PATIENTS. (13th June 2020) - Luque-Tévar, M.; Perez-Sanchez, C.; Pilar, F. U.; Romero-Gómez, M.; Patiño-Trives, A. M.; Ruiz, D.; Arias de la Rosa, I.; Abalos-Aguilera, M. D. C.; Ortega Castro, R.; Escudero Contreras, A.; Rodríguez-Escalera, C.; Pérez Venegas, J. J.; et al.
Abstract : Objectives: To evaluate the changes promoted in levels of circulating inflammatory mediators in RA patients in response to TNF-α inhibitors (TNFi) and anti-CD20 therapies, in order to identify biomarkers of clinical efficacy and potential predictors of therapeutic response to these drugs. Methods: In a prospective RA cohort multicenter study, we collected serum from RA patients with moderate or high disease activity prior and after 6 months of treatment with TNFi or rituximab (RTX), and analyzed levels of 27 proteins that constitute a multi-biomarker test of the inflammatory profile of these samples, using a multiplex immunoassay. Patients' response was determined according to the EULAR response criteria (good/moderate/no). We compared basal levels of inflammatory molecules between the differential response patient groups and analyzed their discriminative ability. Logistic prediction models were created to assess the added value of potential inflammatory predictors. Results: Among 111 total RA patients, 50 of 85 (59%) patients in the TNFi group and 18 of 26 patients in the RTX group (69%) responded to the biologic treatment. High DAS28 or SDAI scores, or titers of auto-antibodies (RF or ACPA) at baseline were not predictive of response to any treatment. Instead, smoking habit and hyperlipidemia at baseline were predictors of a worse response to any of these bDMARDs. Of the molecules analyzed by the multiplex assay, 14 inflammatory mediators showed a significant downregulation on patients' responders to TNFi therapy. Moreover, the decline on 7 biomolecules was related to reduced DAS28. After RTX treatment, 15 inflammatory mediators were reduced in patients with good clinical response; downregulation in 4 of those biomolecules correlated with reduced DAS28. In the search for predictors of response to each bDMARD, by using the MetaboAnalyst software, we could classify patients with distinctive therapeutic response based on the baseline levels of the inflammatory molecules analyzed. Receiver operating characteristic (ROC) analyses for those multiple biomarkers allowed us to further identify specific signatures of inflammatory biomolecules that may serve as predictors of response to each bDMARD therapy with high sensitivity and specificity. Thus, a signature of five molecules was identified as potential predictor of TNFi response [Vascular endothelial growth factor (VEGF), Eotaxin, RANTES, IL7 and IL-17]. Indeed, a signature including three highly expressed cytokines/chemokines in RA serum were identified as predictors of RTX response [interferon-inducible protein 10 (IP10), Eotaxin and monocyte chemotactic protein 1 (MCP-1)]. Conclusion: The extensive analysis of serum inflammatory profile allowed to identify specific and distinctive signatures of biomolecules that, in coordination with known clinical and serological profiles, might predict the response of RA patients to TNFi or RTX treatments. Acknowledgments: Funded by Junta de Andalucía (PI-0285-2017), ISCIII, (PI18/00837 and RIER RD16/0012/0015) co-funded with FEDER Disclosure of Interests: María Luque-Tévar: None declared, Carlos Perez-Sanchez: None declared, Font Ugalde Pilar: None declared, Montserrat Romero-Gómez: None declared, Alejandra M. Patiño-Trives: None declared, Desiree Ruiz: None declared, Iván Arias de la Rosa: None declared, Maria del Carmen Abalos-Aguilera: None declared, Rafaela Ortega Castro: None declared, Alejandro Escudero Contreras: None declared, Carlos Rodríguez-Escalera Speakers bureau: Lilly, GSK, Novartis and Sanofi, José Javier Pérez Venegas: None declared, María Dolores Ruiz Montesinos: None declared, Carmen Dominguez: None declared, Carmen Romero Barco: None declared, Antonio Fernandez-Nebro: None declared, Natalia Mena-Vázquez: None declared, Jose Luis Marenco Speakers bureau: ABbvie, Pfzer, lilly, Julia Uceda: None declared, Mª Dolores Toledo-Coello: None declared, Nuria Barbarroja Puerto Grant/research support from: ROCHE and Pfizer., Speakers bureau: ROCHE and Celgene., Maria A Aguirre: None declared, Chary Lopez-Pedrera Grant/research support from: ROCHE and Pfizer., Eduardo Collantes-Estévez Grant/research support from: ROCHE and Pfizer., Speakers bureau: ROCHE, Lilly, Bristol and Celgene.